Coating material for resisting hydrogen embrittlement in high-temperature environment and preparation method of coating material
By adopting a multi-layer structural design in the coating material, including composite ceramic layer, rare earth doped layer and metal base and oxide composite layer, combined with vacuum sputtering and heat treatment technology, the hydrogen permeation and embrittlement problems in high temperature environments are solved, and the anti-hydrogen embrittlement and oxidation properties of the coating are significantly improved.
Patent Information
- Application Number
- CN202411764809.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
In high temperature environments, it is difficult for existing coating materials to effectively inhibit hydrogen permeation and embrittlement, resulting in degradation of the material's mechanical properties and structural failure.
Using a multi-layer structural design, including composite ceramic layers, rare earth doped layers and metal-based and oxide composite layers, these layers are deposited by vacuum sputtering technology, combined with heat treatment to enhance the coating's anti-hydrogen permeability and oxidation resistance.
It significantly improves the anti-hydrogen embrittlement properties of the coating in high temperature environments, enhances the anti-oxidation and fatigue resistance, extends the service life of the equipment and reduces maintenance costs.
Smart Images

Figure CN119571267A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of coating materials, and in particular relates to a coating material for resisting hydrogen embrittlement in a high temperature environment and a preparation method thereof. Background Art
[0002] Coating materials that are resistant to hydrogen embrittlement in high temperature environments are widely used in gas turbines, petrochemical equipment, nuclear reactors, aerospace and other equipment that have extremely high requirements for high temperature resistance, corrosion resistance and hydrogen embrittlement resistance.
[0003] In high temperature environments, the embrittlement problem caused by hydrogen penetration seriously affects the long-term stability and safety of materials. Hydrogen atoms are more likely to diffuse into the interior of the material at high temperatures, gradually gather and form microcracks, which in turn induce embrittlement, weaken the mechanical properties and fatigue resistance of the material, and ultimately lead to structural failure. Especially in harsh industrial environments such as high temperature and high pressure, highly corrosive gases and frequent thermal cycles, the hydrogen embrittlement problem is particularly serious. In such environments, the hydrogen penetration resistance of conventional coating materials is difficult to meet the requirements. At high temperatures, not only hydrogen penetration will occur, but oxidation reactions and crack propagation are also prone to occur, which will increase the internal stress of the material and aggravate structural degradation, thereby further weakening its strength and toughness. The result is coating shedding, crack propagation and material rupture, which not only affects the reliability of the equipment, but may also cause serious safety hazards, shorten the service life of the equipment and increase maintenance costs.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a coating material for resisting hydrogen embrittlement in a high temperature environment and a preparation method thereof, and solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0007] A method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment comprises the following steps:
[0008] S1: Clean, polish and dry the surface of the substrate;
[0009] S2: Place the cleaned substrate into the vacuum chamber and evacuate to 10 -6 torr, then, installing a composite ceramic layer preparation target, using argon as a sputtering gas, and depositing the composite ceramic layer preparation target onto the surface of the substrate to form a composite ceramic layer preparation;
[0010] S3: replacing the target material, installing the target material for preparing the rare earth doping layer in the vacuum chamber, using argon as the sputtering gas, and depositing the target material for preparing the rare earth doping layer onto the surface of the substrate to form a rare earth doping layer;
[0011] S4: Install the metal-based target and the oxide composite layer target, and keep the vacuum environment at 10 -6 torr, metal matrix and oxide composite layer;
[0012] S5: heat-treating the deposited multilayer coating material in vacuum at a heating rate of 10°C / min to 500°C to 900°C for 1-2 hours;
[0013] S6: After the heat treatment is completed, the coating material is obtained by cooling to room temperature at a cooling rate of 5°C / min.
[0014] Optionally, S1 uses a degreasing agent with a concentration of 5-10% and ethanol for cleaning when cleaning the substrate, the drying temperature is 120° C., the drying time is 30 minutes, and the surface roughness of the substrate after polishing is 0.2-0.5 μm.
[0015] Optionally, the substrate of S1 is one of stainless steel, nickel-based alloy, nickel-based alloy, and nickel-based alloy.
[0016] Optionally, the composite ceramic layer in S2 comprises a composite material of silicon carbide and zirconium oxide, and the mass ratio of silicon carbide to zirconium oxide is 1-3:1.
[0017] Optionally, in S2, when depositing the composite ceramic layer, the sputtering power is 150-300 W, the flow rate of argon gas is 10-20 sccm, the deposition rate is controlled at 5-10 nm / min, the deposition time is 60-120 minutes, and the thickness of the composite ceramic layer is 5-15 μm.
[0018] Optionally, the rare earth oxide in S3 is selected from yttrium oxide, cerium oxide or neodymium oxide configured in equal proportions, and the mass of the doped rare earth oxide is 0.5%-5% of the coating material.
[0019] Optionally, in S3, when depositing the doped layer, the sputtering power is 100-200 W, the flow rate of argon gas is 10-20 sccm, the deposition rate is 2-5 nm / min, the deposition time is 20-60 minutes, and the thickness of the rare earth doped layer is 2-10 μm.
[0020] Optionally, the composite layer comprises a metal-based material and an oxide material, the metal-based material is selected from an alloy of chromium, molybdenum or nickel, the metal-based material in S4 is one of chromium, molybdenum or nickel alloys, the oxide composite layer is one of aluminum oxide or titanium oxide, and the mass ratio of the metal-based material to the oxide material is 2-5:1.
[0021] Optionally, in S4, when preparing the metal-based and oxide composite layer, the vacuum environment is 10 -6torr, the flow rate is 20-30sccm, the flow rate of argon is 20-30sccm, the deposition rate is 5-15nm / min, and the deposition time is 120-200 minutes.
[0022] A method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment is disclosed, wherein the coating material resistant to hydrogen embrittlement in a high temperature environment is prepared.
[0023] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:
[0024] The present invention effectively inhibits the diffusion and aggregation of hydrogen atoms through a multilayer structural design, significantly reducing crack propagation and mechanical property degradation caused by hydrogen embrittlement under high temperature environments. Under the synergistic effect of the composite ceramic layer, the rare earth doping layer, and the metal-based and oxide composite layer, the coating not only greatly enhances the hydrogen permeation resistance, but also improves the oxidation resistance and fatigue resistance, significantly reduces the internal stress accumulation, and effectively prevents the coating from falling off and structural rupture. This coating material can provide more reliable long-term stability and mechanical properties under harsh conditions of high temperature, high pressure, corrosive gas and frequent thermal cycles, greatly prolong the service life of the equipment, reduce maintenance costs, and effectively improve the safety and reliability of operation.
[0025] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0027] In the figure:
[0028] Figure 1 Schematic diagram of the experimental results of coating materials in Examples 1-3.
[0029] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0030] The present invention will now be described in further detail with reference to the accompanying drawings.
[0031] Embodiment 1: In this embodiment, a method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment is provided, comprising the following steps:
[0032] S1: The substrate is stainless steel, and the surface is cleaned with 5% degreasing agent and 99.9% ethanol, and the roughness reaches 0.2μm after polishing. After cleaning, it is dried at 120℃ for 30 minutes.
[0033] S2: Place the substrate into the vacuum chamber and the vacuum degree reaches 10 -6 Silicon carbide and zirconium oxide targets were installed with a mass ratio of 1:1, the sputtering power was set to 150 W, the argon flow rate was 10 sccm, the deposition rate was 5 nm / min, the deposition time was 60 minutes, and a composite ceramic layer with a thickness of 5 μm was formed.
[0034] S3: Replace the target material, install the rare earth oxide target material with equal proportion of yttrium oxide, cerium oxide and neodymium oxide, and maintain the vacuum degree of 10 -6 torr. The sputtering power is 100W, the argon flow rate is 10sccm, the deposition rate is 2nm / min, the deposition time is 20 minutes, the doping layer thickness is 2μm, and the mass of rare earth oxide accounts for 0.5% of the coating.
[0035] S4: Install chromium alloy and alumina targets, the mass ratio of metal base to oxide is 2:1, and the vacuum degree is maintained for 10 - 6 torr. The sputtering power was 200 W, the argon gas flow rate was 20 sccm, the deposition rate was 5 nm / min, and the deposition time was 120 minutes, forming a composite layer with a thickness of 10 μm.
[0036] S5: In a vacuum environment, the temperature is raised to 500°C at a rate of 10°C / min, kept at that temperature for 1 hour, and then cooled to room temperature at a rate of 5°C / min to obtain a hydrogen embrittlement resistant coating material.
[0037] The hydrogen embrittlement resistant coating material prepared in Example 1 was placed in a high temperature environment of 500°C and subjected to a 100-hour hydrogen embrittlement resistance test under controlled conditions. The hydrogen permeability and oxidation generation amount were measured to evaluate the hydrogen resistance of the coating. The specific operation was as follows: the sample was heated to 500°C in a vacuum-sealed system, and the change in hydrogen permeability was measured by a gas permeameter.
[0038] according to Figure 1 As shown in the figure, the hydrogen permeability is reduced by more than 30% and the amount of oxide generation is reduced by 15%. Specifically, the composite ceramic layer and the rare earth doped layer block the diffusion of hydrogen atoms at high temperatures and improve the oxidation resistance of the coating. The composite ceramic layer provides a primary hydrogen barrier effect, the rare earth doped layer further reduces the generation of oxides, and the metal matrix and oxide composite layer enhance the stability of the overall structure. The synergistic effect of these multilayer structures effectively improves the hydrogen embrittlement resistance of the coating in high temperature environments.
[0039] Embodiment 2: In this embodiment, a method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment is provided, comprising the following steps:
[0040] S1: The substrate is a nickel-based alloy, and the surface is cleaned with 8% degreasing agent and 99.9% ethanol, and the roughness reaches 0.4μm after polishing. After cleaning, it is dried at 120℃ for 30 minutes.
[0041] S2: Place the substrate into the vacuum chamber and the vacuum degree reaches 10 -6 Silicon carbide and zirconium oxide targets were installed with a mass ratio of 2:1, the sputtering power was set to 250W, the argon flow rate was 15sccm, the deposition rate was 7nm / min, the deposition time was 90 minutes, and a composite ceramic layer with a thickness of 10μm was formed.
[0042] S3: Replace the target material, install the rare earth oxide target material with equal proportion of yttrium oxide, cerium oxide and neodymium oxide, and maintain the vacuum degree of 10 -6 torr. The sputtering power is 150W, the argon flow rate is 15sccm, the deposition rate is 3.5nm / min, the deposition time is 40 minutes, the doping layer thickness is 5μm, and the mass of rare earth oxide accounts for 2% of the coating.
[0043] S4: Install molybdenum alloy and titanium oxide targets, the mass ratio of metal base to oxide is 3:1, and the vacuum degree is maintained for 10 - 6 torr. The sputtering power was 300 W, the argon gas flow rate was 25 sccm, the deposition rate was 10 nm / min, and the deposition time was 150 minutes, forming a composite layer with a thickness of 15 μm.
[0044] S5: In a vacuum environment, the temperature is raised to 700°C at a rate of 10°C / min, kept at that temperature for 1.5 hours, and then cooled to room temperature at a rate of 5°C / min to obtain a hydrogen embrittlement resistant coating material.
[0045] The prepared coating material samples were placed in a high temperature environment of 700°C and tested for hydrogen embrittlement resistance for 150 hours in a closed vacuum test system. During the test, the hydrogen permeability of the samples was measured regularly using a hydrogen permeameter, and data on the amount of oxide generated on the coating surface was collected through a high temperature oxidation test;
[0046] according to Figure 1As shown in the figure, the experimental results show that the hydrogen permeability of the coating material at 700°C is reduced by more than 40%, and the oxidation generation is reduced by 20%. Specifically, the composite ceramic layer provides an efficient primary hydrogen barrier, while the rare earth doping layer significantly inhibits the oxidation reaction under high temperature conditions. In addition, the metal matrix and oxide composite layer enhance the structural stability and bonding strength of the coating in a high temperature environment, forming a protective barrier that is resistant to high temperature, oxidation, and hydrogen penetration. Therefore, the multilayer structure effectively improves the material's resistance to hydrogen embrittlement in a high temperature environment of 700°C.
[0047] Embodiment 3: In this embodiment, a method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment is provided, comprising the following steps:
[0048] S1: The substrate is titanium alloy, and the surface is cleaned with 10% degreasing agent and 99.9% ethanol, and the roughness reaches 0.5μm after polishing. After cleaning, it is dried at 120℃ for 30 minutes.
[0049] S2: Place the substrate into the vacuum chamber and the vacuum degree reaches 10 -6 torr. Silicon carbide and zirconium oxide targets were installed with a mass ratio of 3:1, the sputtering power was set to 300 W, the argon flow rate was 20 sccm, the deposition rate was 10 nm / min, the deposition time was 120 minutes, and a composite ceramic layer with a thickness of 15 μm was formed.
[0050] S3: Replace the target material, install the rare earth oxide target material with equal proportion of yttrium oxide, cerium oxide and neodymium oxide, and maintain the vacuum degree of 10 -6 torr. The sputtering power is 200W, the argon flow rate is 20sccm, the deposition rate is 5nm / min, the deposition time is 60 minutes, the doping layer thickness is 10μm, and the mass of rare earth oxide accounts for 5% of the coating.
[0051] S4: Install nickel alloy and alumina targets, the mass ratio of metal base to oxide is 5:1, and the vacuum degree is maintained for 10 - 6 torr. The sputtering power was 400 W, the argon gas flow rate was 30 sccm, the deposition rate was 15 nm / min, and the deposition time was 200 minutes, forming a composite layer with a thickness of 25 μm.
[0052] S5: In a vacuum environment, the temperature is raised to 900°C at a rate of 10°C / min, kept at that temperature for 2 hours, and then cooled to room temperature at a rate of 5°C / min to obtain a hydrogen embrittlement resistant coating material.
[0053] The prepared anti-hydrogen embrittlement coating material samples were placed in a high-temperature test environment of 900°C and subjected to a 200-hour long-term hydrogen permeation resistance test in a closed vacuum system. During the experiment, the hydrogen permeability of the samples was regularly monitored by a hydrogen permeation instrument, and the diffusion rate of hydrogen atoms was recorded. At the same time, the oxidation generation of the coating surface was observed and measured through a high-temperature oxidation test;
[0054] according to Figure 1 As shown in the figure, the experimental results show that at an extremely high temperature of 900°C, the hydrogen permeability of the coating material is reduced by more than 55%, and the amount of oxidation generated is reduced by 30%. Specifically, the thicker composite ceramic layer significantly blocks the diffusion of hydrogen, while the rare earth doping layer effectively reduces the oxidation reaction rate at extremely high temperatures and improves the oxidation resistance. At the same time, the metal matrix and oxide composite layer enhance the overall bonding strength and structural stability of the coating, forming a solid anti-permeation barrier at a high temperature of 900°C. Therefore, the multilayer structure ensures the excellent hydrogen embrittlement resistance of the coating in an extremely high temperature environment and extends the service life of the material.
[0055] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment, characterized in that: The following steps are involved: S1: Clean, polish and dry the surface of the substrate; S2: Place the cleaned substrate into the vacuum chamber and evacuate to 10 -6 torr, then, installing a composite ceramic layer preparation target, using argon as a sputtering gas, and depositing the composite ceramic layer preparation target onto the surface of the substrate to form a composite ceramic layer preparation; S3: replacing the target material, installing the target material for preparing the rare earth doping layer in the vacuum chamber, using argon as the sputtering gas, and depositing the target material for preparing the rare earth doping layer onto the surface of the substrate to form a rare earth doping layer; S4: Install the metal-based target and the oxide composite layer target, and keep the vacuum environment at 10 -6 torr, metal matrix and oxide composite layer; S5: heat-treating the deposited multilayer coating material in vacuum at a heating rate of 10°C / min to 500°C to 900°C for 1-2 hours; S6: After the heat treatment is completed, the coating material is obtained by cooling to room temperature at a cooling rate of 5°C / min.
2. The method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment according to claim 1, characterized in that: The materials used for cleaning the substrate of S1 are degreasing agent with a concentration of 5-10% and ethanol cleaning, the drying temperature is 120°C, the drying time is 30 minutes, and the surface roughness of the substrate after polishing is 0.2-0.5 μm.
3. The method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment according to claim 1, characterized in that: The base material of S1 is one of stainless steel, nickel-based alloy, nickel-based alloy, and nickel-based alloy.
4. The method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment according to claim 1, characterized in that: The composite ceramic layer in S2 comprises a composite material of silicon carbide and zirconium oxide, and the mass ratio of silicon carbide to zirconium oxide is 1-3:
1.
5. The method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment according to claim 1, characterized in that: In S2, when depositing the composite ceramic layer, the sputtering power is 150-300 W, the flow rate of argon gas is 10-20 sccm, the deposition rate is controlled at 5-10 nm / min, the deposition time is 60-120 minutes, and the thickness of the composite ceramic layer is 5-15 μm.
6. The method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment according to claim 1, characterized in that: The rare earth oxide in S3 is selected from yttrium oxide, cerium oxide or neodymium oxide configured in equal proportions, and the mass of the doped rare earth oxide is 0.5%-5% of the coating material.
7. The method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment according to claim 1, characterized in that: In S3, when depositing the doped layer, the sputtering power is 100-200 W, the flow rate of argon gas is 10-20 sccm, the deposition rate is 2-5 nm / min, the deposition time is 20-60 minutes, and the thickness of the rare earth doped layer is 2-10 μm.
8. The method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment according to claim 1, characterized in that: The composite layer comprises a metal-based material and an oxide material, wherein the metal-based material is selected from an alloy of chromium, molybdenum or nickel, the metal-based material in S4 is one of chromium, molybdenum or nickel alloys, and the oxide composite layer is one of aluminum oxide or titanium oxide, and the mass ratio of the metal-based material to the oxide material is 2-5:
1.
9. The method for preparing a coating material resistant to hydrogen embrittlement in a high temperature environment according to claim 1, characterized in that: In S4, the vacuum environment is 10 -6 torr, the flow rate is 20-30sccm, the flow rate of argon is 20-30sccm, the deposition rate is 5-15nm / min, and the deposition time is 120-200 minutes.
10. A coating material for resisting hydrogen embrittlement in a high temperature environment prepared by the method for preparing a coating material for resisting hydrogen embrittlement in a high temperature environment according to any one of claims 1 to 9.
Citation Information
Cited By
Method for resisting hydrogen embrittlement through ultrasonic impact surface treatment and application
CN121852656A